2011
DOI: 10.1115/1.4003230
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of Turning Flow Effects on Innovative Pin Fin Arrangements for Trailing Edge Cooling Configurations

Abstract: The effect of the array configuration of circular pin fins is investigated from a numerical and experimental point of view reproducing a typical cooling scheme of a real high pressure aero-engine blade. The airstream enters the domain of interest radially from the hub inlet and exits axially from the trailing edge (TE) outlet section. More than 100 turbulators are inserted in the wedge-shaped TE duct to enhance the heat transfer: A reference array implementing seven rows of staggered pins is compared with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Liao et al [5] in their study on pin-fin arrangement, found that the Nusselt number decreases with increasing the ratio between lengths to diameter of pin-fins. Bianchini et al [6] investigated arrangement of pin fins with circular cross-section. Kelkar et al [7] investigated the staggered pins on parallel plates forming a channel.…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al [5] in their study on pin-fin arrangement, found that the Nusselt number decreases with increasing the ratio between lengths to diameter of pin-fins. Bianchini et al [6] investigated arrangement of pin fins with circular cross-section. Kelkar et al [7] investigated the staggered pins on parallel plates forming a channel.…”
Section: Introductionmentioning
confidence: 99%
“…Metzger et al [2] and [3] experimentally studied the flow and heat transfer characteristics of a rectangular channel with short pin-fins at Reynolds number varying from 10,000 to 50,000, pin streamwise spacing ratio 1.32 to 2.5, and imposed empirical correlations between average array Nusselt number, pin fins spacing and Reynolds number. For the case where the trailing edge is convergent (wedge-shaped), most studies focused on the influence of the outlet of cold air [4], Reynolds number [4], the layout of pinfins [4][5][6], and the shape of pin-fins [7][8][9] on heat transfer and flow resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The flow becomes very complex, unsteady, and turbulent. A clear estimation of these phenomena is not easily obtained when using experimental measurement [1]. Furthermore, when considering turbines blades, the flow is subjected to rotation, strongly influencing streamlines and heat transfer.…”
Section: Introductionmentioning
confidence: 99%